Sytuacja kobiet na rynku pracy w czasie pandemii - Ewa Krause (Edukacja Ustawiczna Dorosłych)
This article is an attempt to present the situation of women on the labor market during the COVID-19 pandemic. The study was performed with the desk research method. The existing data (world and national) concerning the issues related to the situation was analyzed. Professional activities of women and their presence in managerial positions were also discussed in order to show gender inequalities existing regardless of the current crisis. The scientific community and the situation of women academics/scientists were also referred to as confirmation of the deterioration of the position of women in the Coronavirus era. The results of the study indicate that the crisis related to the COVID-19 pandemic is gender-specific and exposes the social inequalities which especially affect women. Due to the pandemic, the labor market situation of women is precarious and even more difficult than before the Coronavirus outbreak.